The comprehensive study of the Antarctic Ice Sheet in the area of Vostok Research Station - S. A. Ignatyev; A. V. Bolshunov; D. A. Vasiliev; G. D. Gorelik; N. S. Krikun; D. V. Serbin; V. G. Kadochnikov (Лëд и снег)
.